Composition and volume of municipal fisheries catch in six coastal barangays of Liloan, Cebu, Philippines - Sungcad, Amanda Thea R. (2016)
The coastal area of Liloan that is composed of six barangays is a source of continuous supply of fishes since the municipality is surrounded by known fish habitats. Over the years, there have been a lot of changes in the environment that could have led to a decline in fish catch. Since there is insufficient local data on fish catch volume and taxonomic composition, it is challenging to develop conservation and long-term management plans without knowing what species or subpopulations are involved. This study aimed to determine the relative composition of demersal and pelagic fish catch according to family, the average volume of catch per day of municipal fishermen, and the kind of elasmobranchs, rays, and endangered coral reef fish caught. Through an extensive one-on-one interview of 90 all male fishermen respondents, it was found that currently the total catch per day ranges from 0 to 10 kg. Family Mullidae is the most abundant demersal fisheries (16%) while Family Carangidae is the most abundant pelagic fisheries (35%). Among the surgeonfishes, Nasolopezi is the most caught fish (15%). Species Epinepheluscoioides (10%) had the highest fish count among all the other species of groupers. Two endangered species, Cheilinus undulates and Bolbometoponmuricatumare still caught. Wobbegong is the most abudant (14%) from the elasmobranchs while reticulate whipray from the rays (24%). In the fish intercept, Family Siganidae is the most abundant demersal fisheries (20%) while Family Carangidae is the most abundant pelagic fisheries (23%). The fish intercept result were mostly in agreement with the data generated from the one- on-one interview.
Thesis (Bachelor of Science in Biology). University of the Philippines Cebu